On-Site Earthquake Early Warning System as an Alternative Earthquake Mitigation Solution in Indonesia - Bali, Ika (President University, 2023)
The Banten earthquake, which had a magnitude of 6.6 on January 14, 2022, damaged 3,078 houses. Thatnumber consisted of 395 heavily damaged units, 692 moderately damaged units and 1,991 lightly damaged units(Tempo.co, 2022). The Banten earthquake was a strong earthquake where the magnitude was greater than a scale of5. Damage to houses caused by the earthquake occurred in most single-story houses or low-rise buildings. Given thelarge number of one-story houses that are damaged every time a major earthquake occurs in Indonesia, there needs tobe appropriate mitigation measures to reduce the risk of earthquake disasters, especially for human casualties. AnOn-site Earthquake Early Warning System (On-site EEWS) can be an alternative in reducing victims of the disaster.This earthquake early warning system has sensors that are installed on the site of building houses and can predictstrong earthquake waves that are destructive in nature (S/Secondary Waves) through P/Primary Waves that arriveearly in about 10-20 seconds. This time is sufficient for evacuation for the occupants of a one-story house if the earlywarning alarm is properly responded to. This early warning radius can reach 20 km from the on-site EEWS locationconsidering that this area has relatively the same vibration effect. Currently, Indonesia through the BMKG isdeveloping EEWS as a part of the existing earthquake mitigation system. The purpose of this study is to describe theapplication of an on-site earthquake early warning system as an alternative solution for earthquake mitigation inIndonesia. This study evaluates several EEWS applications in the literature to find the best alternative to be appliedin Indonesia. The critical factors for on-site implementation of the EEWS discussed in this paper are compared withthe Taiwan regional EEWS. Based on the existing validation, the on-site EEWS has an 80% accuracy rate inpredicting the intensity level of a strong earthquake, capable to automatically send an alarm message within 3seconds and providing a warning time of at least 8 seconds before a destructive peak S wave arrives.